SAT0392 IMPLEMENTING THE PSORIATIC ARTHRITIS DISEASE ACTIVITY SCORE (PASDAS) IN ROUTINE CLINICAL PRACTICE: (IM)POSSIBLE?. (June 2019) - Mulder, Michelle; Broeder, Alfons den; Ginneken, Berbke van; Vriezekolk, Johanna; Mahler, Elien; Hoogen, Frank van den; Wenink, Mark
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous disease, with involvement of at least five health domains: peripheral joint disease, enthesitis, dactylitis, axial involvement, and skin and nail psoriasis. Because of the heterogeneity of the disease, assessment of disease activity is challenging. One of the many single or composite outcome measures that has been developed is the Psoriatic Arthritis Disease Activity Score (PASDAS). The PASDAS is a comprehensive measure that takes arthritis (66/68 joint score), dactylitis, enthesitis, CRP, physician disease activity VAS score and patient-reported outcomes into account 1 . Furthermore, it is a continuous outcome measure in contrast to the Minimal Disease Activity criteria (MDA), facilitating the longitudinal follow-up of disease activity. The PASDAS also has better parametric distribution and discriminative capacity compared to other outcome measures such as the Disease Activity for PSoriatic Arthritis score (DAPSA). However, feasibility of PASDAS use in routine clinical care has been questioned due to its complexity. It requires a CRP and filled-out SF36 form at time of assessment, does not include a formal skin assessment, is difficult to calculate and is time consuming for both patient and physician. Objectives: To implement PASDAS measurements and skin assessments in routine clinical care for all 1300 PsA patients treated at our centre. Methods: The implementation consisted of the following stages: 1) assessment of patients' acceptability of measurement burden; 2) implementation of mathematical calculations of the PASDAS in our electronic health record; 3) PASDAS and skin assessment training of rheumatology nurses and rheumatologists; and 4) (logistic) adjustments to the outpatient visit. Results: Our patient partners preferred comprehensive clinical assessment of skin and joints above a limited assessment (such as the DAS28-CRP), although the latter would be less time consuming. For this reason, and to comply with international guidelines, we decided to also add assessment of skin disease, by using the Body Surface Area (BSA) and Physician Global Assessment score (PGA). Furthermore, research demonstrated that for the PASDAS calculation the physical component score (PCS) of the SF36 could be substituted by the SF12-PCS 2 . As the SF12 is more concise, minimizing patient burden, we chose to implement the SF12 instead of the SF36. The SF12-PCS, together with the other separate component scores and corresponding mathematical calculation of the PASDAS, was implemented in our electronic health record. Lastly, we set-up a three phase consultation that consists of laboratory tests and consultation with a rheumatology nurse who performs the physical measurements before each visit with the physician. Conclusion: Standardized and routine measurement of the PASDAS and skin involvement at each outpatient visit of all our PsA patients before consultation with the treating rheumatologist was successfully implemented, underscoring the feasibility of this approach. In addition to improving clinical care, routine outcome measurements can be used for a variety of clinical studies. References: [1] Helliwell, P.S., et al., The development of candidate composite disease activity and responder indices for psoriatic arthritis (GRACE Project). Ann of the Rheum Dis. 2013 Jun;72(6):986-91. [2] Helliwell, P.S, et al., Modification of the Psoriatic Arthritis Disease Activity Score (PASDAS). Ann Rheum Dis. 2018 Mar;77(3):467-468. Disclosure of Interests: Michelle Mulder: None declared, Alfons den Broeder: None declared, Berbke van Ginneken: None declared, Johanna Vriezekolk: None declared, Elien Mahler: None declared, Frank van den Hoogen: None declared, Mark Wenink Consultant for: abbvie